Pan-cancer analysis of the mediator complex transcriptome identifies CDK19 and CDK8 as therapeutic targets in advanced prostate cancer - Brägelmann, Johannes; Duensing, Stefan (Clinical cancer research, 2017)
Purpose: The Mediator complex is a multiprotein assembly, which serves as a hub for diverse signaling pathways to regulate gene expression. Because gene expression is frequently altered in cancer, a systematic understanding of the Mediator complex in malignancies could foster the development of novel targeted therapeutic approaches. Experimental Design: We performed a systematic deconvolution of the Mediator subunit expression profiles across 23 cancer entities (n = 8,568) using data from The Cancer Genome Atlas (TCGA). Prostate cancer-specific findings were validated in two publicly available gene expression cohorts and a large cohort of primary and advanced prostate cancer (n = 622) stained by immunohistochemistry. The role of CDK19 and CDK8 was evaluated by siRNA-mediated gene knockdown and inhibitor treatment in prostate cancer cell lines with functional assays and gene expression analysis by RNAseq. Results: Cluster analysis of TCGA expression data segregated tumor entities, indicating tumor-type-specific Mediator complex compositions. Only prostate cancer was marked by high expression of CDK19. In primary prostate cancer, CDK19 was associated with increased aggressiveness and shorter disease-free survival. During cancer progression, highest levels of CDK19 and of its paralog CDK8 were present in metastases. In vitro, inhibition of CDK19 and CDK8 by knockdown or treatment with a selective CDK8/CDK19 inhibitor significantly decreased migration and invasion. Conclusions: Our analysis revealed distinct transcriptional expression profiles of the Mediator complex across cancer entities indicating differential modes of transcriptional regulation. Moreover, it identified CDK19 and CDK8 to be specifically overexpressed during prostate cancer progression, highlighting their potential as novel therapeutic targets in advanced prostate cancer. Clin Cancer Res; 23(7); 1829-40. ©2016 AACR.
Published online first September 27, 2016
Gesehen am 12.06.2018